قـراءة النـص الشعـري بنيـويا مقاربة نظرية وتطبيقية - عـروس, محمـد (قــــــراءات; No 07-06 (2014): (مجلة قراءات( نوفمبر, 2019)
تسهدف هذه الدراسة الكشف عن الآليات  الاجرائية التي تسمح بتحليل النص الشعري من وجهة نظر بنيوية، ذلك أن المنهج البنيوي هدفه البحث عن العلاقات التي تنشأ بين العناصر المكونة للنص مثل : بنية القرابة التي لا نمسك بها إلا في العلاقة  بين عنصرين أو أكثر مثل علاقة الأخوة أو الأبوة. و لذلك يسعى المنهج البنيوي إلى بيان كيف تتحق الدلالة بالبحث في العلاقات بين العناصر النصية و تحديده البنية العامة أو البنيات الجزئية للنص أما الدلالة ذاتها فلا تهم المحلل البنيوي. إن سؤال المنهج البنيوي هو كيف؟ أما السؤال لماذا فمؤجل، و عليه فما هي الآليات الاجرائية التي يمكن بواسطتها تحليل النص الشعري من منظور المنهج البنيوي؟ Abstract This study aims to reveal the procedural mechanisms which allow to analyze the poetic text according to a structural point of view, since the subject of the structural method is to find relationships between the different elements of the text; as an example the structure of consanguinity which we can only find through a relations between two members or more such as fraternity and paternity. As a result, the structural method isoriented toshow whether it can be semantic or not when looking into relations between the elements of the text and to precise the main structure as well as the sub-structure of the chosen text. Regarding to the semantic itself, it’s not relevant to the structural analyzer. The main question of the structural method is How. As for the question Why,it’s postponed .Therefore, what are the procedural mechanisms that may lead to the analysis of the poetic text through the structural method vision?